The role of Augmentative and Alternative Communication in Speech and Language Therapy: A mini review - Ayesha Kamal Butt; Rabia Zubair; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2022)
Augmentative and Alternative Communication is an aided or unaided means of communication which supports existing communication abilities of an individual or replaces natural speech due to any speech and language disorder. The deficit could be developmental or acquired such as autism spectrum disorder, cerebral palsy, learning difficulties, dysarthria, dyspraxia or due to any acquired neurological condition such as aphasia and other degenerative disorders. Furthermore, it may be due to surgical procedures such as laryngectomy. Alternate means of communication have also been successfully used with COVID-19 patients. These tools may include pictures, symbols, signs or voice output devices. Parents of children with special needs and medical professionals have been reluctant in implementing the approach due to certain misconceptions. The aim of this review is to summarize the current evidence for the use of Augmentative and Alternative Communication with a range of disorders in relation to in relation to Pakistan. Keywords: Assistive technology, Aided communication, Complex communication needs, Early intervention, Speech generating devices, Speech and language intervention Continue...